The Effects of Board Gender Quotas: A Meta-Analysis - Costanza De Acutis; Andrea Weber; Elisabeth Wurm (Institute of Labor Economics (IZA), 2024)
We use a meta-analysis to summarize the recent literature evaluating effects of the introduction of gender quotas on company boards. We collect data from 51 studies on policies implemented in 11 countries from which we extract 496 estimates. The literature considers the effects of quota policies on a wide range of outcome variables which we group in four categories. The findings of the meta-analysis contribute to the discussion of boardroom quota policies by mitigating some concerns of negative impacts and pointing out areas where more policy action is needed.
Keywords: C8; G3; J7; 330; corporate governance; diversity; gender quota; meta-analysis